(untitled) (Eurasian Journal of Ecology, 2023)
Global food security is of particular concern, so agricultural production will need to increase significantly to meet the food needs of growing populations. Increased crop yields can be achieved through the adoption and improvement of nutrient management and fertilizer technology. Results of field research have shown, that unilateral use of increasing doses of nitrogen fertilizers and their combination with phosphorus and potassium provide vegetative activity of potato plants: in accumulation of dry biomass, an increase of leaf area and photosynthetic productivity, that finally was integrated into formation of high yields of tubers - 37,8-45,4 t/ha at 32,4 t/ha in control plots. The obtained regression model reflects adequately enough (R=0,886) the experimental data. The application of mineral fertilizers decreased the share of a small fraction of tubers down to 6,0 - 8,7 % in potato yield, while increasing the share of large fractions up to 55-69 %. Depending on different doses of fertilizers potato plants accumulated 172,2 to 260,6 kg/ha of nitrogen, 63,3 to 84,1 kg/ha of phosphorus, and 197,0 to 256,3 kg/ha of potassium in biomass. On average, potato plants used 66 % of nitrogen, 26 % of phosphorus, and 59 % of potassium from fertilizers. For 1 ton tuber production, potatoes taken up 4.4 - 5.8 kg of nitrogen, 1.6 - 2.0 kg of phosphorus and 4.6 - 6.1 kg of potassium, depending on the doses and ratios of fertilizers.The effect and interaction of nitrogen, phosphorus, and potassium fertilizers on the normative intake of nutrients by potatoes are described quite adequately (R = 0,727-0,885) by regression models. Economic efficiency of application of fertilizers was high in the treatments where increasing doses of nitrogen were combined with small doses of potassium, and in the treatment with doses of fertilizers applicated for planned yield - 5102,6-5769,9 tenge/ha at relatively low production cost - 50,1-56,5 tenge/kg and high profitability of production - 123,1-149,7 %. Key words: potato, light chestnut soil, fertilizers, yield, regression, economic efficiency.